Social and Health-Related Factors Associated with Enrollment to Medicare Advantage Plans in Older Adults - Kumar, Amit (J Am Geriatr Soc, 2019)
OBJECTIVE: We assessed the characteristics of older Mexican American enrollees in traditional Fee-For-Service (FFS) and Medicare Advantage (MA) plan and the factors associated with disenrollment from FFS and enrollment in MA plans. DESIGN: Longitudinal study linked with Medicare claims data. SETTING: Community-dwelling Mexican American older adults (N=1455) participating in the Hispanic Established Populations for the Epidemiologic Study of the Elderly. MEASUREMENTS: We examined insurance status using the Medicare Beneficiary Summary File and estimated the association sociodemographic and clinical factors with insurance plan switching. RESULTS: Among Mexican American older adults, FFS enrollees were more likely to be born in Mexico, speak Spanish, have lower levels of education, and have more disability than MA enrollees. Older adults with a larger number of IADL limitations (OR; 0.50, 95% Confidence Interval [CI]: 0.26 - 0.98) and more social support (OR; 0.70, 95% CI: 0.45-0.98) were less likely to switch from FFS to MA compared to older adult with no limitations and less social support. Additionally, older adults living in counties with a greater number of MA plans were more likely to switch from FFS to MA (OR; 2.1, 95% CI: 1.45-3.16), compared to counties with a lower number of MA plans. In counties with higher number of MA plans, older adults with more social support had lower odds of switching from FFS to MA (OR; 0.48, 95%CI: 0.28-0.82) compared to older adults with less social support. CONCLUSION: Compared to those enrolled in MA, older Mexican American adults enrolled in Medicare FFS are more socioeconomically disadvantaged and are more likely to demonstrate poor health status. Stronger social support and increased physical limitations were strongly associated with less frequent switching from FFS and to MA plans. Additionally, increased availability of MA plans at the county level is a significant driver of enrollment in MA plans.